Bilateral anterior dislocation in the hips: a case report - Dheeraj Makkar; Ravi Sauhta (Journal of Trauma and Injury)
The hip is a stable ball-and-socket joint. Bilateral anterior dislocations of the native hip joints account for fewer than 1% of all dislocations. We present a unique case of a bilateral anterior dislocation in a patient who presented to our institution within 6 hours of trauma. The dislocations were promptly reduced under propofol anesthesia in the operating room. The patient did not suffer a concurrent fracture. After the procedure, we performed regular X-ray examinations for 2 years to rule out the development of avascular necrosis of the head of the femur. The course of the patient was unremarkable.